A new mixed finite element analysis of the elastodynamic equations. (September 2016) - García, Carlos; Gatica, Gabriel N.; Meddahi, Salim
Abstract: The main results on a new mixed finite element analysis for linear elastodynamics with reduced symmetry are described in this paper. The model is formulated as a second order system in time in which the main unknowns are given by the Cauchy stress tensor and the rotation. Well-posedness of the resulting variational formulation, as well as unique solvability and convergence results for a conforming semi-discrete scheme and a fully discrete version employing the Newmark trapezoidal rule, are presented.